Child dietary diversity and food (in)security as a potential correlate of child anthropometric indices in the context of urban food system in the cases of north-central Ethiopia - Amare Molla Dinku; Tefera Chane Mekonnen; Getachew Shumye Adilu (BMC, 2020)
Abstract Objective To investigate the relation of child dietary diversity and household food insecurity along with other socio-demographic with child anthropometric indices in north-central Ethiopia, an area with a high level of food insecurity and inadequate diet quality. Design A community-based cross-sectional study was used. Settings The study was conducted in Dessie and Combolcha towns of north-central Ethiopia from April to May 2018. Participants Randomly selected 512 mother-child pairs with child's age range of 6-59 months. Results The mean (± SD) scores of weight-for-height/length, height/length-for-age, weight-for-age, and BMI-for-age Z-scores were 1.35 (± 2.03), − 1.89 (± 1.79), 0.05 (± 1.54), and 1.39 (± 2.06), respectively. From all anthropometric indicators, stunting and overweight/obesity remained the severe public issues hitting 43% and 42% of the children, respectively. In the model, mothers' age and education and child's age, sex, and dietary diversity were significantly related with child height-for-age Z-score while place of residence, sex of household head, child's age, and dietary diversity score were the predictors of child BMI-for-age Z-score in the urban contexts of the study area. Nevertheless, food insecurity was not related to any of the child anthropometric indices. Conclusion The double burden of malnutrition epidemics (stunting and obesity) coexisted as severe public health concerns in urban settings. Anthropometric statuses of children were affected by multidimensional factors and seek strong integration and immediate intervention of multiple sectors.